Pengalaman Intercultural Adjustment Mahasiswa Indonesia di Jepang - Putu Satwika Arya Govinda; Yuliana Hanami (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2023)
The cultural differences encountered while studying abroad can trigger problems that generate negative emotions. To prevent the negative impact of these emotions on the quality of life of students, it is important to have intercultural adjustments so that they can deal with cultural differences more adaptively. This study aims to explore the obstacles experienced by Indonesian students in Japan and how intercultural adjustment efforts are made. The research was conducted using descriptive qualitative methods through semi-structured interviews with two Indonesian students in Japan. Data analysis using thematic analysis. The results of the study found several themes of obstacles such as language barriers, difficulty socializing with local people, living systems due to differences in weather and climate, loneliness, and difficulty finding halal food. To overcome these obstacles, several themes of adjustment were made, including: emotional regulation, self opening, flexible, and evaluating new experiences and knowledge. These themes show that the adjustment of Indonesian students in Japan can be explained within the framework of intercultural adjustment.